The position of the accused in investigation in some historical models of criminal procedure - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In the short first section, the author points out that the investigation is crucial for the trial and because of this the position of the accused in investigation is of utmost importance. This also justifies the analysis of the accused’s position in four historical models of criminal proceedings.The second section is concerned with the position of the accused in investigation of Roman law.The third section discusses the position of the accused in early feudal criminal proceedings when neither official nor private investigation in the contemporary form existed. The fourth section is devoted to the position of the accused in the inquisitorial procedure.The fifth section deals with the position of the accused in the investigation of a mixed type process of the early nineteenth century.In the brief conclusion the author highlights that there is no straight line evolution of the accused’s position in investigation. The historical models rather show its raises and falls. The current position of the accused in investigation is certainly far more favourable than it was in the examined historical models of criminal proceedings.